Efficiency and Ropiness of Traditional White and Ultrafilteration Cheese as Affected by Psycrotroph Bacteria - ALLAH MIRZAEI†, H.; EZZATI, R.; DEZYANI*, M. (Asian Journal of Chemistry, 2009)
During cheese ripening, some of water insoluble casein change to water soluble nitrogen which include intermediate hydrolyzate protein and free amino acids. In this work, ripening and efficiency of traditional white cheese and ultrafilteration cheese as affected by Psycrotroph bacteria was investigated. The result showed that amount of Psycrotroph bacteria on the white and ultrafilteration cheese was significant. Also, there was a good correlation between Psycrotroph bacteria and ratio of soluble nitrogen to total nitrogen during ripening period. In fact, as the Psycrotroph bacteria increase, the ratio of soluble nitrogen to total nitrogen increased during ripening period. The per cent of N recovery (efficiency index) for ultrafilteration and traditional white cheese was 88.01-90.45 and 77.23-80.52, respectively. The effect of changing above parameter on ultrafilteration cheese is more than white cheese.